2017
DOI: 10.1371/journal.pcbi.1005725
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering HLA-I motifs across HLA peptidomes improves neo-antigen predictions and identifies allostery regulating HLA specificity

Abstract: The precise identification of Human Leukocyte Antigen class I (HLA-I) binding motifs plays a central role in our ability to understand and predict (neo-)antigen presentation in infectious diseases and cancer. Here, by exploiting co-occurrence of HLA-I alleles across ten newly generated as well as forty public HLA peptidomics datasets comprising more than 115,000 unique peptides, we show that we can rapidly and accurately identify many HLA-I binding motifs and map them to their corresponding alleles without any… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
293
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(305 citation statements)
references
References 55 publications
11
293
0
1
Order By: Relevance
“…Here, we repeated this benchmark analysis using NetMHCpan-4.0. The results are shown in figure 10 and confirm the finding by Bassani-Sternberg et al (14), that predictors trained on MS eluted ligand data information in most cases show very high predictive power for the identification of cancer neoantigens. Both the NetMHCpan-4.0 and MixMHCpred method proposed by Bassani-Sternberg et al (14) identify the known neoantigens within the top 25 peptides in 6 out out 10 cases.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Here, we repeated this benchmark analysis using NetMHCpan-4.0. The results are shown in figure 10 and confirm the finding by Bassani-Sternberg et al (14), that predictors trained on MS eluted ligand data information in most cases show very high predictive power for the identification of cancer neoantigens. Both the NetMHCpan-4.0 and MixMHCpred method proposed by Bassani-Sternberg et al (14) identify the known neoantigens within the top 25 peptides in 6 out out 10 cases.…”
Section: Resultssupporting
confidence: 86%
“…This large number of potential peptide candidates clearly underlines the need for tools to rationally downsize the peptide space in the search for cancer neoepitopes. A recent study by Bassani-Sternberg et al (14) demonstrated how this downsizing could be effectively achieved by a prediction method trained on a large set of MS eluted ligands. Here, we repeated this benchmark analysis using NetMHCpan-4.0.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations